Language Laboratory Management in Improving Students English Speaking Ability - Delli Sabudu; Joulanda A.M Rawis; Mozes Markus Wullur; Viktory N.J. Rotty; Uus Kamajaya Al Katuuk (Institut Agama Islam Negeri (IAIN) Curup, 2021)
Proficiency in English is one type of ability to be achieved in teaching English because English is an international language and the main means of communicating with westerners and understanding English books. So it is necessary to optimize learning and teaching English in formal and non-formal education institutions. This research aims at finding out whether or not English laboratory Management affects students’ achievement. As one of basic skills, speaking involves oral and written features. English laboratory may refer to conventional computer uses or the Computer Assisted Language Laboratory (CALL) in the process of English teaching. The English Department of Universitas Negeri Manado uses modern form of language laboratory teaching. The research was conducted in the Department of English in which its population was taken from the first semester students appearing in the academic year 2020/2021 and sitting in five classes and each class had twenty five students. The result is supported by the data showing tobs>ttable (P = 0.05); (df = 48) 8,031 > 2,010(P = 0.05); (df = 48). If t- observed < t-table, the null hypothesis (Ho) is accepted and the alternative hypothesis (Ha) is rejected. There is a difference mean score obtained from both of controlled group at 67 showing 46% and the experimental group reaches 80,08 referring to 59.02 %. The students who had treatment in English laboratory management use successfully got higher score than students who did not have treatment about such management use. So it may conclude that the Language Laboratory management plays an important role in the success of learning English, especially to improve students' English speaking skills.